2021
DOI: 10.3892/etm.2021.10284
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and associated cell signalling pathways underlying the anticancer properties of phytochemical compounds from Aloe species (Review)

Abstract: Naturally occurring components from various species of Aloe have been used as traditional folk medicine since the ancient times. Over the last few decades, the therapeutic effects of extracts and phytochemical compounds obtained from Aloe vera have been proven in preclinical and clinical studies. Recently, compounds from other Aloe species apart from Aloe vera have been investigated for the treatment of different diseases, with a particular focus on cancer. In the present review, the effects of phytochemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 169 publications
(300 reference statements)
1
4
0
Order By: Relevance
“…The ferric chloride test exhibited the presence of phenols, whereas the foam test showed the presence of saponins. Eight classes (alkaloids, flavonoids, glycosides, saponins, sterols, terpenoids, phenols and fixed oils and fats) of phytocompounds were found in the leaf extract of A. ferox across the study sites, which was consistent with the previous studies (Nalimu et al 2021;Singh et al 2021;Svitina, Hamman & Gouws 2021). The leaf extracts also revealed the presence of fixed oils and fats.…”
Section: Resultssupporting
confidence: 90%
“…The ferric chloride test exhibited the presence of phenols, whereas the foam test showed the presence of saponins. Eight classes (alkaloids, flavonoids, glycosides, saponins, sterols, terpenoids, phenols and fixed oils and fats) of phytocompounds were found in the leaf extract of A. ferox across the study sites, which was consistent with the previous studies (Nalimu et al 2021;Singh et al 2021;Svitina, Hamman & Gouws 2021). The leaf extracts also revealed the presence of fixed oils and fats.…”
Section: Resultssupporting
confidence: 90%
“…Within the same study, it is noted that a concentration of 80 μM is sufficient to block the activity of Phosphatidylinositol (4,5) bisphosphate [75]. On the other hand, it has been shown that Quercetin induces the inactivation of the AKT protein, an anti-apoptotic protein, by decreasing its phosphorylation and also directly inactivates procaspase-9, thus blocking cellular apoptosis [76]. In addition, exposure of cells to a concentration of 50 μM resulted in the blockade of the Extracellular Signal-Regulated Kinases (ERK1/2) pathway.…”
Section: Cancermentioning
confidence: 88%
“…In this regard, Aloe vera -based nanoformulations activate different metabolic pathways linked to apoptosis, including but not limited to Bax, Bad, and Caspase signaling. Thus, nanoformulations containing compounds from Aloe vera induce ROS production, followed by increased levels of p-ERK1/2, p-p38, and p-JNK [ 153 , 155 ].…”
Section: Discussion and Perspectives On The Use Of Aloe Ver...mentioning
confidence: 99%